Adjuvant chemotherapy for lymph node positive esophageal squamous cell cancer: The prediction role of low mean platelet volume - Liu, Xiaoling; Zhang, Kaijiong; Tang, Jie; Jiang, Li; Jiang, Yu; Wang, Qifeng (Frontiers in Oncology, 2022)
Background This study aimed to examine whether MPV is a useful prognostic marker and investigated whether MPV is a risk factor that helps identify patients with locally advanced-stage ESCC who will most likely benefit from adjuvant chemotherapy. Methods Patients (n =1690) with histologically confirmed ESCC were diagnosed with locally advanced stage (pT3-4N0M0 and pT1-4N+M0) at Sichuan Cancer Hospital from 2009 to 2017. Clinicopathological factors and platelet-related values were tested for their associations with survival using univariate and multivariate Cox regression analyses. The optimal cut-off value for continuous variables was determined using the ‘maxstat’ R package. The KM curve continuous variable analysis was performed to identify the optimal cut-off value for MPV. Cumulative survival rates were determined using the Kaplan–Meier estimator and compared using the log-rank test. The survival analysis was performed using the ‘survival’ R package. All statistical analyses were performed using R software 4.1.3 (https://www.r-project.org/), and a two-sided p-value <0.05 was considered to indicate statistical significance. Results Multivariate analysis indicated that low MPV was an important risk factor for overall survival in locally advanced ESCC, independent of classic clinicopathological factors. The optimal cut-off value of MPV (11.8 fL) was used to stratify high-risk patients. Patients with low mean platelet volumes had a worse prognosis than those with larger platelet volumes, according to Kaplan–Meier analysis and the log-rank test. Patients diagnosed with a pathological lymph node-positive stage with a low MPV (≤11.8 fL) benefited from postoperative chemotherapy, but not those with a high-level MPV (>11.8 fL). Conclusion MPV served as an independent predictor of prognosis of locally advanced-stage ESCC and predicted a survival benefit conferred by postoperative adjuvant chemotherapy in lymph node-positive ESCC.